Solitary fibrous tumor: A center's experience and an overview of the symptomatology, the diagnostic and therapeutic procedures of this rare tumor - Hohenforst-Schmidt, Wolfgang (Respir Med Case Rep, 2017)
Solitary Fibrous Tumor of the Pleura (SFTP) is a rare tumor of the pleura. Worldwide about 800 patients diagnosed with this oncological entity have been described in the existing literature. We report our center's 13 year experience. During this time three patients suffering from this rare disease have been treated in our department. All patients were asymptomatic and their diagnosis was initially triggered by a random finding in a routine chest x-ray. The diagnosis was set preoperatively through a needle biopsy under computer tomography (CT) guidance. The tumors were resected surgically though video-assisted thoracoscopic surgery (VATS) or thoracotomy. Because of the lack of specific guidelines due to the rarity of the disease a long-term, systematic follow-up was recommended and performed. Parallel an overview of the diagnostic and therapeutic procedures of the rare tumor is made.